Onset of magnetic order in YbCu5-xAlx - Bauer, E.; Hauser, R.; Keller, L.; Fischer, P.; Trovarelli, O.; Sereni, J.G.; Rieger, J.J.; Stewart, G.R.; Sereni, Julián (American Physical Society, 1997)
Fil: Trovarelli, O. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina